Dividends and asymetric information: analysis of the new market (Revista de Administração, 2012)
In December 2000, the São Paulo Stock Exchange, Bovespa, created a special listing for companies that voluntarily accepted additional corporate governance practices beyond those required by the Securities and Exchange Commission (CVM). The purpose of this innovation was to establish a closer relationship between companies and their investors, reducing information asymmetry and enhancing investor protection. The aim of this paper was to test the effects of this initiative on asymmetric information in the stock market. To this end, a study of events was conducted, using the dividend policy as the main variable. The results show that companies that entered the market with different degrees of governance have lower levels of information asymmetry, thus having placed themselves in a more secure institutional environment. Therefore, Bovespa's initiative was successful in mitigating the asymmetric information problem of the Brazilian stock market.